2007
DOI: 10.1160/th07-03-0197
|View full text |Cite
|
Sign up to set email alerts
|

The appended tail region of heparin cofactor II and additional reactive centre loop mutations combine to increase the reactivity and specificity of α1-proteinase inhibitor M358R for thrombin

Abstract: SummaryNatural inhibitors of coagulation or inflammation such as the serpins antithrombin (AT), heparin cofactor II (HCII), and 1-proteinase inhibitor (α1-PI) can be overwhelmed in thrombosis and/or sepsis. The reactive centre (P1-P1) variant α1-PI M358R inhibits not only procoagulant thrombin but also anticoagulant activated protein C (APC). We previously described HAPI M358R, comprising a fusion of HCII residues 1–75 to the N-terminus of a1-PI M358R that yielded increased anti-thrombin, but not anti-APC acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…In both reports, these investigators expressed a truncated form of API M358R in E. coli, one lacking its N-terminal 12 residues [53]. We expressed both API M358R and the LS7-3/P′2L variant, which we designated “API RCL5”, in a hexahistidine-tagged, full length recombinant API protein, finding, that it was less active than API M358R, in our hands by about 13% [30]. Thus, it is uncertain whether or not API variants with increased activity versus thrombin have been synthesized, prior to this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In both reports, these investigators expressed a truncated form of API M358R in E. coli, one lacking its N-terminal 12 residues [53]. We expressed both API M358R and the LS7-3/P′2L variant, which we designated “API RCL5”, in a hexahistidine-tagged, full length recombinant API protein, finding, that it was less active than API M358R, in our hands by about 13% [30]. Thus, it is uncertain whether or not API variants with increased activity versus thrombin have been synthesized, prior to this study.…”
Section: Discussionmentioning
confidence: 66%
“…Pre-clinical studies demonstrated further refinements in specificity and activity were required prior to contemplating this protein as a therapeutic agent in individuals prone to overactive coagulation [24]–[26]. Both our laboratory and other groups have made some progress in this regard by using mutagenesis strategies in which additional residues from other serpins were substituted into the API M358R [27][30].…”
Section: Introductionmentioning
confidence: 99%
“…pro-thrombotic) functions of NSP. Serpins are suicide inhibitors forming 1:1 stoichiometric complexes, wherein the protease cleaves the serpin RCL P1-P1Ј scissile bond, forming a complex with the serpin such that both the serpin and protease lose function after binding (1)(2)(3)(4)(5)29). These active peptides may represent a class of anti-inflammatory peptides similar to the highly active expanding classes of defensin peptides.…”
Section: Discussionmentioning
confidence: 99%
“…This same RCL can insert into the neighboring ␤-sheet A in other serpins in serpinopathies, causing serpin aggregates induced by genetic mutations and causing disease as for anti-thrombin III (SERPIN C1, ATIII), ␣-1 antitrypsin (SERPIN A1, AAT), and neuroserpin (SERPIN I1, NSP). Whereas the amino acid residues in the RCL provide target P1-P1Ј sequences, referred to as a scissile bond, serpins also require the greater part of the protein structure to function with true serpin-protease inhibitory activity (4,5). However, as for other proteins, peptides derived during protein metabolism may act to extend serpin activity beyond the initial suicide-inhibitory function, both increasing and decreasing responses (6 -9).…”
mentioning
confidence: 99%
“…While this change elicited a bleeding tendency in the index case (Owen et al, 1983), it sparked interest in using the API scaffold to generate novel protease inhibitors by protein engineering. Directed mutagenesis approaches have met with some success in enhancing the specificity of API for nonphysiological targets, but typically at the cost of elevating the reaction stoichiometry (Dufour et al, 2001;Dufour et al, 2005;Filion et al, 2004;Sutherland et al, 2007). Random mutagenesis approaches involving the screening of hypervariable serpin expression libraries has until recently been employed only in the case of one serpin, plasminogen activator inhibitor 1 (PAI-1) (Pannekoek et al, 1993;Stoop et al, 2001Stoop et al, , 2000van Meijer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%